Acute and chronic functional and traditional resistance training improve muscular fitness in young males via the AMPK/PGC-1α/irisin signaling pathway - Chongwen Zuo; Xiaoyan Ma; Chaoqun Ye; Zhiyang Zheng; Shumin Bo (Komiyama Printing Co. Ltd, 2023)
Background: In this study, we aimed to investigate the effects of acute and chronic resistance training of varying intensities on molecular responses and their association with muscular fitness in a cohort of young males who participated in this intervention study. Methods: Young males (19-28 years) with no prior training experience underwent a six-week program consisting of two distinct modalities of resistance training. The participants were randomly divided into a functional resistance training group (FRT; n = 9; participants performed 4-5 sets of 20 repetitions maximum (RM) at 40% 1RM) or a traditional resistance training group (TRT; n = 9; participants performed 4-5 sets of 12 RM at 70% 1RM). Both protocols entailed training three days per week for six weeks. Blood samples were obtained before, immediately after an acute bout of training, and after the six-week training program to determine alterations in molecular responses. Muscular fitness analysis and anthropometric measurements were conducted before and after the six-week training program. Results: After the six-week training program, the lean body mass of participants in both TRT and FRT groups was significantly increased (p < 0.05), whereas body fat percentage and fat mass were significantly decreased solely in the FRT group (p < 0.05). All muscular fitness variables were significantly increased in both groups (p < 0.01), with no difference between the two groups. Additionally, in the TRT group, serum levels of AMP-activated protein kinase (AMPK) were significantly increased following acute training and six weeks of resistance training, whereas in the FRT group, no significant increase in serum levels of AMPK was observed. In both groups, serum levels of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α), irisin, and insulin-like growth factor-1 were significantly increased. Moreover, myostatin was significantly decreased following acute training and six weeks of resistance training (p < 0.05), with no difference between the two groups. Furthermore, a significant correlation was observed between barbell back squat and certain molecular variables. Conclusions: Overall, our study indicates that acute and chronic resistance training of varying intensities are effective changing molecular responses, the chronic FRT and TRT improve muscular fitness in young males through the AMPK/PGC-1α/irisin signaling pathway. Trial registration: Chinese Clinical Trial Registry: ChiCTR2200059775 (11/05/2022).